1998
DOI: 10.1159/000007474
|View full text |Cite
|
Sign up to set email alerts
|

Increased Hepatocyte Growth Factor Content in Rat Stomach during Omeprazole Treatment

Abstract: Background and Aims: Hepatocyte growth factor (HGF) is a potent mitogen of gastric epithelial cells, and its production is stimulated during the healing of gastric mucosal lesions. In this study, the effect of a proton pump inhibitor, omeprazole, on the production and degradation of HGF in the stomach was examined to elucidate the mechanism of the omeprazole-induced acceleration of gastric mucosal healing. Methods: Indomethacin-induced gastric mucosal lesions were induced in rats with or without omeprazole pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“… HGF gene expression in small (1–6) or large (7–12) MNP of normal (1, 7) and acutely injured liver isolated at 6 h (2, 8), 12 h (3, 9), 24 h (4, 10), 48 h (5, 11) or 72 h (6, 12) after the application of CCl 4 . Total RNA was extracted from freshly isolated MNP and analysed by Northern blotting.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… HGF gene expression in small (1–6) or large (7–12) MNP of normal (1, 7) and acutely injured liver isolated at 6 h (2, 8), 12 h (3, 9), 24 h (4, 10), 48 h (5, 11) or 72 h (6, 12) after the application of CCl 4 . Total RNA was extracted from freshly isolated MNP and analysed by Northern blotting.…”
Section: Resultsmentioning
confidence: 99%
“… Modulation of HGF gene expression in cultured large MNP of normal rat liver. Large MNP were cultured for 1 day and treated with TNF‐α 100‐U/ml (2), TNF‐α 1000‐U/ml (3), interferon‐α 1000‐U/ml (4), or interferon‐γ 1000‐U/ml (6). Lanes 1 and 5 controls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other reports have suggested that several growth factors are involved in the ulcer healing effects of PPIs. In this regard, Kinoshita et al (1998) observed that the gastric levels of HGF were enhanced by omeprazole in rats with indomethacin-induced gastric damage. Moreover, the expression of EGF was found to be increased in the gastric mucosa of mice with indomethacin-induced injury, and further enhanced by omeprazole (Banerjee et al, 2008).…”
Section: Effects Of Ppis On Gastric Mucosal Protection and Ulcer Healingmentioning
confidence: 93%
“…Artificial ulcers generated in rats lead to the release of growth factors at the topical site of the mucosa. Several of the growth factors, such as the hepatocyte growth factor, are activated only in acidic milieu, and ulcer healing is paradoxically prolonged in the absence of acid in animal models [102]. …”
Section: Gastric Acid and Digestive And Mucosal Processesmentioning
confidence: 99%